Influence of Corporate Governance On Profit of Islamic Banks in Indonesia Period 2016-2020 - Erwin Saputra Siregar; Muhamad Subhan; Rahmi Mardhatillah (Jurnal Ilmiah Ekonomi Islam, 2021)
Profitability in Islamic banks is one of the most critical elements. Meanwhile, corporate governance becomes the central aspect of Islamic banks in the company's internal management, including the quality of financial statements that have implications for profitability. The small proportion of independent boards of commissioners, audit committees, and board of directors leads to a potential decrease in profits at Islamic banks in Indonesia. This phenomenon is caused by the management of companies, including Islamic banks, less responding to the situation. The independent variables of this research are the proportion of separate boards of commissioners, audit committees, and boards of directors. At the same time, the dependent variable is profit. The data used in secondary data is the annual report of Islamic banks in Indonesia in 2016-2020. The analysis method uses multiple regression analysis of panel data. This study showed that the audit committee affected profits while the proportion of independent boards of commissioners and directors did not affect profits.